Damage model based on gradient property method for simulating the tensile behavior of composite laminates with Variable Angle Tow reinforcement. (February 2020) - Qi, Shijie; Shi, Pengcheng; Yan, Chun; Imran, Ali; Liu, Dong; Zhu, Yingdan; Herrmann, Axel S.
Abstract: In this work Tailored Variable Angle Tow (VAT) patches with various layup directions are employed to reinforce open-hole carbon fiber composite laminates and the tensile behaviour of the reinforced laminates is investigated. The relationship between the tensile behaviour of the reinforced laminate and the fiber orientation of the VAT reinforcement is revealed by experiments. Moreover, this paper proposes a multi-scale finite element model to simulate the reinforced laminate under tensile load. The multi-scale model, consisting of a unit cell model and a gradient property model, is designed to characterize the constitutive response of VAT composites with various fiber fractions and gradient properties. The comparison of the simulation and experimental results indicates that the model not only provides accurate computed tensile strength with the deviation less than 6%, but also presents failure mode predictions that in accordance with the experimental results.